MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN AKTIVITAS SISWA MENGGUNAKAN KOMBINASI MODEL PBL, TALKING STICK, DAN TPACK: Penelitian Tindakan Kelas - Melanie Veronika; Radiansyah (STKIP Subang, 2024)
Critical thinking abilities, activities and student learning outcomes which are still relatively low are problems in this research. With this problem, research was carried out with the aim of improving students' critical thinking skills, activities and learning outcomes. This research carried out was classroom action research which took place in class 4 of SDN 1 Tamiang Layang with 25 students. The results of the research showed that from the three meetings conducted by researchers it was known that teacher activity obtained a percentage of 96% in the